(untitled) (Global Journal of Human-Social Science, 2020)
This study aims to investigate the impact of educational level on the Langauge difference within the Saudi community. In this study, all Saudi citizens who live in Jeddah city represented the population of the study. The study based on a quantitative research design. Sixty persons from various educational levels were the participants of the study. A questionnaire used as a data collection instrument; the mean scores evaluated according to the Lickert 5-point scale. A pilot study conducted by selecting a sample of size (20) individuals from the population of the study, to test the questionnaire reliability and validity. The descriptive analysis was employed to analyze the quantitative data collected via the questionnaire using the Statistical Package for the Social Sciences (SPSS). Based on data analysis conducted in this study, the researcher concluded with the following findings: There is a strong relationship between education levels and language differences .2. Education levels effect the language differences within the Saudi community-Jeddah city. Finally, the researcher recommended the following recommendations. The decision and policymakers in the educational field should consider the results of this study in their annual curriculums review. 2. The researcher should conduct further investigation in the future to generalize the results of the survey in all-over the Kingdom of Saudi Arabia.